PENGARUH PEMANFAATAN SARANA DAN PRASARANA PEMBELAJARAN DENGAN TINGKAT PRESTASI MAHASISWA DI UNIHAZ - Nurmintan Silaban (UNIVERSITAS BENGKULU, 2016)
The research objective was to determine the effect of the completeness of facilities and infrastructure of learning in higher education towards student achievement UNIHAZ. This studyuses a quantitative approach. Research was carried UNIHAZ students enrolled as an active student in the second semester of FY 2014/2015 and respondent selection will be determined by proportionate random sampling. Collecting data using questionnaires previously tested the validity and reliability testing. Data analysis using simple linear regression. Conclusion of research is a significant difference between the use of learning facilities and infrastructure to the level of interpretation.Keywords : learning , achievement , facilities and infrastructure